2015
DOI: 10.1177/0731684415592484
|View full text |Cite
|
Sign up to set email alerts
|

The effect of silica nanotubes on mechanical performance of polymethyl methacrylate nanocomposites: Comparison to spherical nano-silica

Abstract: Silica nanotubes (SNTs) were synthesized via sol-gel method using ammonium tartrate as template, and then spherical nano-silica (SiO 2 ) and SNTs which have different geometric morphology were introduced into polymer matrix to obtain polymethyl methacrylate (PMMA)/SiO 2 and PMMA/SNTs microspheres via in situ suspension polymerization, respectively. The morphology of synthesized SNTs and microspheres were observed by scanning electron microscope (SEM), while the structure of SiO 2 and SNTs, as well as the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Silica nanotubes have been use to reinforce PMMA polymer matrix and the results showed that the composite material had greater mechanical properties. 46 It has been shown 47 that scaffolds fabricated using silica nanotubes supported osteoblast cell spreading and proliferation.…”
Section: Silica Nanotubesmentioning
confidence: 99%
“…Silica nanotubes have been use to reinforce PMMA polymer matrix and the results showed that the composite material had greater mechanical properties. 46 It has been shown 47 that scaffolds fabricated using silica nanotubes supported osteoblast cell spreading and proliferation.…”
Section: Silica Nanotubesmentioning
confidence: 99%